A comprehensive grid to evaluate case management's expected effectiveness for community-dwelling frail older people: results from a multiple, embedded case study. Issue 1 (December 2015) - Van Durme, Thérèse; Schmitz, Olivier; Cès, Sophie; Anthierens, Sibyl; Maggi, Patrick; Delye, Sam; De Almeida Mello, Johanna; Declercq, Anja; Macq, Jean; Remmen, Roy; Aujoulat, Isabelle
Abstract Background Case management is a type of intervention expected to improve the quality of care and therefore the quality of life of frail, community-dwelling older people while delaying institutionalisation in nursing homes. However, the heterogeneity, multidimensionality and complexity of these interventions make their evaluation by the means of classical approaches inadequate. Our objective was twofold: (i) to propose a tool allowing for the identification of the key components that explain the success of case management for this population and (ii) to propose a typology based on the results of this tool. Methods The process started with a multiple embedded case study design in order to identify the key components of case management. Based on the results of this first step, data were collected among 22 case management interventions, in order to evaluate their expected effectiveness. Finally, multiple correspondence analyses was conducted to propose a typology of case management. The overall approach was informed by Wagner's Chronic Care Model and the theory of complexity. Results The study identified a total of 23 interacting key components. Based on the clustering of response patterns of the 22 case management projects included in our study, three types of case management programmes were evidenced, situated on a continuum from a more "socially-oriented" type towards a more "clinically-oriented" type of case management. The type of feedback provided to the general practitioner about both the global geriatric assessment and the result of the intervention turned out to be the most discriminant component between the types. Conclusion The study design allowed to produce a tool that can be used to distinguish between different types of case management interventions and further evaluate their effect on frail older people in terms of the delaying institutionalisation, functional and cognitive status, quality of life and societal costs.